PENGARUH MODEL SUDU OVERLAP DAN HELIX PADA PROSES INISIASI PUTARAN TURBIN SAVONIUS - Witono, Kris; Nasir, Moh.; Faizal, Elka; Wicaksono, Hangga; Pranoto, Bayu (Otopro, 2019)
This research proposes a new model of overlap and helix blade shape. The overlap shape of the blades gives room to the air flow shortly after pounding the blades. Air flow direction is strived to be able to push the next blade so that the process of the turbine blade rotation becomes more effective. While the helix model is expected to produce a more efficient turbine rotation due to its multilevel shape. The wind speeds tested were 2 m / s, 4 m / s, and 6 m / s. Turbine speed rotation data retrieval is carried out at each additional time. The overlap blade has a greater angular velocity value of 9.4 rad / s at 2 m / s wind speed, 21.9 rad / s at 4 m / s wind speed, and 29.8 rad / s at 6 m / s wind speed.Turbines with multilevel helix blades have a higher level of stability compared to overlap blades. This is because there are two levels of turbine blades which have an angle difference of 600 which can receive more stable wind collisions. However, due to the smaller cross-sectional area of the helix blade turbine (ie 50% of the overlap blade) the effective impact area on the blade is also getting smaller. So that the energy that can be converted is also relatively smaller than the overlapping blade.